Development of a Sensing Array for Human Breath Analysis Based on SWCNT Layers Functionalized with Semiconductor Organic Molecules. Issue 12 (6th May 2020) - Freddi, Sonia; Emelianov, Aleksei V.; Bobrinetskiy, Ivan I.; Drera, Giovanni; Pagliara, Stefania; Kopylova, Daria S.; Chiesa, Maria; Santini, Giuseppe; Mores, Nadia; Moscato, Umberto; Nasibulin, Albert G.; Montuschi, Paolo; et al.
Abstract: A sensor array based on heterojunctions between semiconducting organic layers and single walled carbon nanotube (SWCNT) films is produced to explore applications in breathomics, the molecular analysis of exhaled breath. The array is exposed to gas/volatiles relevant to specific diseases (ammonia, ethanol, acetone, 2‐propanol, sodium hypochlorite, benzene, hydrogen sulfide, and nitrogen dioxide). Then, to evaluate its capability to operate with real relevant biological samples the array is exposed to human breath exhaled from healthy subjects. Finally, to provide a proof of concept of its diagnostic potential, the array is exposed to exhaled breath samples collected from subjects with chronic obstructive pulmonary disease (COPD), an airway chronic inflammatory disease not yet investigated with CNT‐based sensor arrays, and breathprints are compared with those obtained from of healthy subjects. Principal component analysis shows that the sensor array is able to detect various target gas/volatiles with a clear fingerprint on a 2D subspace, is suitable for breath profiling in exhaled human breath, and is able to distinguish subjects with COPD from healthy subjects based on their breathprints. This classification ability is further improved by selecting the most responsive sensors to nitrogen dioxide, a potential biomarker of COPD. Abstract : A sensor array based on heterojunctions between semiconducting organic layers and carbon nanotube (CNT) films is produced to explore applications in the field of breathomics, i.e., the molecular analysis of exhaled breath. The array is successfully validated on the diagnostics of chronic obstructive pulmonary disease, a major lung disease so far not yet investigated with CNT‐based arrays.